169 Dasotraline for Treatment of Adults with Binge-Eating Disorder: Effect on Binge-related Obsessions and Compulsions. (April 2020) - Citrome, Leslie; Goldman, Robert; Tsai, Joyce; Deng, Ling; Grinnell, Todd; Pikalov, Andrei
Abstract: Background: Binge-eating disorder (BED), the most common eating disorder in the US, is frequently associated with impairment in quality of life and functioning. Dasotraline, a long-acting dopamine/norepinephrine reuptake inhibitor, has a PK profile characterized by slow absorption and an elimination half-life of 47-77 hours, and is dosed once-daily. In a recent placebo-controlled, flexible-dose study, dasotraline demonstrated significant efficacy in patients with BED. We now report an analysis from this study of the effect of dasotraline on binge-related obsessions and compulsions. Method: Patients with moderate-to-severe BED, based on DSM-5 criteria, were randomized to 12 weeks of double-blind, placebo controlled, treatment with flexible doses of dasotraline (4, 6, and 8 mg/d). The primary efficacy measure was number of binge-eating days/week; secondary measures included the Binge Eating Clinical Global Impression of Severity (BE-CGI-S) score and the Yale-Brown Obsessive-Compulsive Scale Modified for Binge-Eating (Y-BOCS-BE), a validated, 10-item interviewer-administered measure designed to assess the severity of obsessional thoughts and compulsive behaviors related to binge eating. Change from baseline in efficacy measures in the Intent-to-treat (ITT) population were analyzed using a mixed model for repeated measures (MMRM) analysis. Results: The ITT population consisted of 317 patients (female, 84%; mean age, 38.2 years). LS mean reduction from baseline in number of Binge Eating (BE) days per week was significantly greater for dasotraline vs. placebo at week 12 (-3.74 vs. -2.75; P<0.0001; effect size [ES] = 0.74; primary endpoint); week 12 change was significantly greater for dasotraline vs. placebo on the Y-BOCS-BE total score (-17.05 vs. -9.88; P<0.0001; ES, 0.96), the obsession subscale score (-8.32 vs. -4.58; P<0.0001; ES, 0.95), and the compulsion subscale score (-8.69 vs. -5.35; P<0.0001; ES, 0.87). All 10 YBOCS-BE items were significantly improved on dasotraline vs. placebo at week 12 (P<0.001 for all comparisons; with effect sizes ranging from 0.54 to 0.90). At Week 12 (LOCF), for dasotraline and placebo, 52.3% and 18.4% of patients, respectively, had a BE-CGI-S score of 1 ("normal; not at all ill"; NNT=3). At endpoint, for patients with a global illness severity score of 1, the corresponding mean Y-BOCS-BE total scores were 0.5 and 0.7 for dasotraline and placebo, respectively, indicating that when BED illness severity approaches "normal, not at all ill", binge-related obsessions and compulsions demonstrate comparably low levels of severity. Conclusion: In this placebo-controlled, 12-week study of patients with moderate-to-severe binge eating disorder, treatment with dasotraline (4-8 mg/d) was associated with significant and clinically meaningful reduction in binge-related obsessional thoughts and compulsive behaviors. Clinicaltrials.gov number: NCT02564588 Funding Acknowledgements: Supported by funding from Sunovion Pharmaceuticals Inc.